1982
DOI: 10.3177/jnsv.28.377
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of phospholipid and triglyceride metabolism in fatty liver caused by pyridoxine deficiency in rats.

Abstract: SummaryWhen weanling rats were given 70% casein diet deficient in pyridoxine, they showed marked accumulation of liver lipid consisting mainly of triglyceride (TG) and cholesterol ester (CE). The serum concentrations of phospholipid (PL) and cholesterol (CH) in pyridoxine deficient rats were significantly lower than those in pair-fed controls, but their serum levels of TG and free fatty acid (FFA) were not significantly different from those of controls. A significant inverse relation was shown between the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…4,28,29) In addition, serum PC concentration was significantly lower in B 6 -deficient rats than in pair-fed controls. 29) In an analogous fashion, Kaimoto et al 30) reported that about 50% of rats fed a diet supplemented with branched-chain amino acids during B 6 deficiency showed lipid deposition in the liver and tended to have decreased serum TG levels. Moreover, they found that rats with liver lipid deposition also had decreased TG and TC levels in VLDL.…”
Section: Discussionmentioning
confidence: 96%
“…4,28,29) In addition, serum PC concentration was significantly lower in B 6 -deficient rats than in pair-fed controls. 29) In an analogous fashion, Kaimoto et al 30) reported that about 50% of rats fed a diet supplemented with branched-chain amino acids during B 6 deficiency showed lipid deposition in the liver and tended to have decreased serum TG levels. Moreover, they found that rats with liver lipid deposition also had decreased TG and TC levels in VLDL.…”
Section: Discussionmentioning
confidence: 96%
“…4 ) However, Suzuki and Okada 5 ) observed a decreased level of PC in vitamin B 6 -deficient rat liver in spite of addition of sufficient choline to the diet. They indicated that the utilization of choline might be impaired by vitamin B6 deficiency, presumably because of reduced activity of choline phosphokinase (EC 2.7.1.32).…”
mentioning
confidence: 99%